2016
DOI: 10.1002/ejp.965
|View full text |Cite
|
Sign up to set email alerts
|

Mu and delta opioid receptor knockout mice show increased colonic sensitivity

Abstract: Knockout mice for mu and delta opioid receptor have augmented colon sensitivity in the CRD assay. It shows endogenous mu and delta opioid analgesia that may be explored as potential targets for alleviating chronic intestinal pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 59 publications
2
14
0
Order By: Relevance
“…Opioid peptides are constitutively produced by mucosal immune cells in steady-state conditions but their production is not sufficient to inhibit abdominal pain upon acute colitis. 18,21,[27][28][29][30] By contrast, chronic F I G U R E 5 CD4 + T lymphocytes from IL-10 −/− mice activated under nonpolarizing conditions produce lesser amounts of PENK mRNA than those from wild-type. Naïve CD4 + T lymphocytes isolated from either wild-type (IL-10 +/+ ) or IL-10 −/− mice were activated with a cocktail of anti-CD3 and anti-CD28 antibodies for 6 d. Proliferation was monitored by analyzing CellTrace Violet dispersion in live CD4 + T cells before (A) and on days 3 (B) and 6 (C) following activation (left panels).…”
Section: Discussionmentioning
confidence: 94%
“…Opioid peptides are constitutively produced by mucosal immune cells in steady-state conditions but their production is not sufficient to inhibit abdominal pain upon acute colitis. 18,21,[27][28][29][30] By contrast, chronic F I G U R E 5 CD4 + T lymphocytes from IL-10 −/− mice activated under nonpolarizing conditions produce lesser amounts of PENK mRNA than those from wild-type. Naïve CD4 + T lymphocytes isolated from either wild-type (IL-10 +/+ ) or IL-10 −/− mice were activated with a cocktail of anti-CD3 and anti-CD28 antibodies for 6 d. Proliferation was monitored by analyzing CellTrace Violet dispersion in live CD4 + T cells before (A) and on days 3 (B) and 6 (C) following activation (left panels).…”
Section: Discussionmentioning
confidence: 94%
“…[21] Even though the mechanisms underlying visceral pain share some homology with somatic pain, both are still not fully elucidated yet. According to the study performed by Reiss et al, [25] mice deficient in MOP and DOP are more prone to pressure stimulus compared with their wild-type littermates in the mouse model of CRD. Overall quality of life in IBS patients is diminished, and the inefficiency of drugs could further decrease it.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, Larsson et al [24] demonstrated that the selective KOP-agonists U-69593 (5 and 25 mg/kg, s.c.) and asimadoline (25 mg/kg, s.c.) significantly decreased the VMR in mice lacking KOP, while having no effect in control mice. According to the study performed by Reiss et al, [25] mice deficient in MOP and DOP are more prone to pressure stimulus compared with their wild-type littermates in the mouse model of CRD. This, along with our results, strengthens the importance of opioid receptors in colon sensitivity and paves the way for development of future treatment options in IBS.…”
Section: Resultsmentioning
confidence: 99%
“…33,34 This inhibits the release of proinflammatory and algesic neuropeptides in the periphery and at the dorsal horn of the spinal cord, reducing neurogenic inflammation and nociception, respectively. Chronic inflammation is associated with the peripheral release of opioids from mucosal CD4+ T cells.…”
Section: Enkephalinase Inhibitionmentioning
confidence: 99%
“…These opioids activate mu and delta opioid receptors expressed on sensory afferent terminals, activation of which leads to a suppression of action potential firing and to reduced sensitivity. 33,34 This inhibits the release of proinflammatory and algesic neuropeptides in the periphery and at the dorsal horn of the spinal cord, reducing neurogenic inflammation and nociception, respectively. 1.…”
Section: F I G U R Ementioning
confidence: 99%